(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
The forensic toxicologist faces many problems to find out various seeds used in the criminal cases. In the rural area’s mainly farmers use poisonous seeds to commit suicide and to find analysis of that seed is very difficult task to forensic toxicologist. And the easiest method to find is Thin Layer Chromatography. This technique helps to forensic toxicologist to solve any criminal cases of toxicology. The main purpose in the thin layer chromatography is to find the RF’ value and analyses the content by various solvent systems. By analyzing the seeds which we find at crime scene and thin layer chromatography is performed to give the results. The solvent system is found and Rf valve of the sample is found in this overall review. This review has made the forensic toxicologist the easiest task to solve any criminal activities related to crime in the criminal proceedings.